Avaliação de métodos diagnósticos, morfológicos e biomolecularesem mulheres encaminhadas com citologia alterada - Denise Gasparetti Drumond (2006)
The purpose of this study, which was based on women with abnormal cytology when screening for cervical cancer who were led from different units of the Public Health System to the reference university service and with a definite diagnosis of high cervical intraephitelial neoplasia or cancer, was to evaluate the diagnostic efficacy of morphologic and molecular methods used alone or together and the prevalence of HPVtypes 16,18,45, stratified into two age brackets. For this study, 167 women went to the Cervical Pathology and colposcopy clinic of the University Hospital of the Federal University of Juiz de Fora, during the period from November of 2002 to December of 2003, with hole cervical part of the uterus, not pregnant and without previous chemicaland/or radiotherapy treatment for the inferior genital tract. Samples for cytology study were collected from all women, with conventional and liquid-based preparations, for CH2® for high risk virus, for DNA PAP® and for Probe Pack ® test. The worst histologic diagnosis among the possible histologic studies through biopsy, conization or cirurgic pieces was considered as gold standard. The results showed that there is nodifference regarding sensibility, positive predict value and negative predict value for all methods studied. However, the DNA PAP® method has less specifics than the cytology exam, either with conventional or based-liquid preparation. The prevalence of HPV 16, 18, 45 decreases from 88,9% to 50% in women of 30 years old or more, being this decrease statistically significant. Thus, in those women led to the PTGIC of the HUUFJFwith abnormal cytology is not necessary to repeat any exam, just colposcopy in order to reach the final diagnosis.